Envelhecimento e cuidado em disputa: entre a mercantilização da vida e o cuidado integral como direito social: https://doi.org/10.60543/ts_iss.vi10.11508 ("Temas Sociais" Journal, 2026)
Human aging and healthcare are not neutral or homogeneous processes but are shaped by competing societal and health policy projects. This theoretical-critical essay examines contemporary conceptions of aging through the tensions between biologicist and economic approaches, on the one hand, and sociocultural and comprehensive perspectives, on the other. Aging should not be understood as a natural stage of the life course experienced equally by all individuals. Rather, it is a continuous process shaped by historical and social conditions, including cultural, socioeconomic, and structural factors that accumulate throughout life and become manifest in old age. By discussing the ethical, political, and institutional implications of these conceptions for the care of older people, the essay problematizes the naturalization of family responsibility and the retreat of the State from the field of care. In this context, it argues that care should be understood as a social right and as a relational and ethical practice that should guide the organization of comprehensive responses, thereby contributing to dignity and the right to age.